Literary rhetoric : concepts-structures-analyses - Plett, Heinrich F. (International Studies in the History of Rhetoric, 2010)
Dedicated to the subject of literary rhetoric, this book is divided in three principal parts: I. An historical outline of the relationship of rhetoric and literature. II. An overview of the realm of rhetoric and its parts and functions, above all in the section of \'elocutio\' with its classes of figures, where a critical comparison of traditional and modern models of the rhetorical figures is followed by the design of a new one. III. The implementation of this new concept in seven classes of figures and their respective subdivisions: 1. phonological, 2. morphological, 3. syntactic, 4. semantic, 5. graphemic, 6. textological, and 7. intertextual figures. Each chapter is supplemented by analyses of literary texts conceived as a demonstration of the applicability of the theoretical concepts and structures presented before. An extensive bibliography of research literature and detailed indices of names and subjects conclude this treatise.